Situation Report: Hungary, 20 March 1973 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Increased Control of Enterprise Investments Problems with the Child Welfare Allowance 1973 Hungarian-Chinese Trade Agreement Signed Attacks on China Closed Production System Increases Agricultural Output The Agricultural Situation in the Spring of 1973